Anticancer property of Bryophyllum pinnata (Lam.) Oken. leaf on human cervical cancer cells - Mahata, Sutapa (BioMed Central, 2012)
BACKGROUND: Bryophyllum pinnata (B. pinnata) is a common medicinal plant used in traditional medicine of India and of other countries for curing various infections, bowel diseases, healing wounds and other ailments. However, its anticancer properties are poorly defined. In view of broad spectrum therapeutic potential of B. pinnata we designed a study to examine anti-cancer and anti-Human Papillomavirus (HPV) activities in its leaf extracts and tried to isolate its active principle. METHODS: A chloroform extract derived from a bulk of botanically well-characterized pulverized B. pinnata leaves was separated using column chromatography with step- gradient of petroleum ether and ethyl acetate. Fractions were characterized for phyto-chemical compounds by TLC, HPTLC and NMR and Biological activity of the fractions were examined by MTT-based cell viability assay, Electrophoretic Mobility Shift Assay, Northern blotting and assay of apoptosis related proteins by immunoblotting in human cervical cancer cells. RESULTS: Results showed presence of growth inhibitory activity in the crude leaf extracts with IC(50 )at 552 μg/ml which resolved to fraction F4 (Petroleum Ether: Ethyl Acetate:: 50:50) and showed IC(50 )at 91 μg/ml. Investigations of anti-viral activity of the extract and its fraction revealed a specific anti-HPV activity on cervical cancer cells as evidenced by downregulation of constitutively active AP1 specific DNA binding activity and suppression of oncogenic c-Fos and c-Jun expression which was accompanied by inhibition of HPV18 transcription. In addition to inhibiting growth, fraction F4 strongly induced apoptosis as evidenced by an increased expression of the pro-apoptotic protein Bax, suppression of the anti-apoptotic molecules Bcl-2, and activation of caspase-3 and cleavage of PARP-1. Phytochemical analysis of fraction F4 by HPTLC and NMR indicated presence of activity that resembled Bryophyllin A. CONCLUSIONS: Our study therefore demonstrates presence of anticancer and anti-HPV an activity in B. pinnata leaves that can be further exploited as a potential anticancer, anti-HPV therapeutic for treatment of HPV infection and cervical cancer.